ACTION REASEARCH: KEMAMPUAN GERAKAN RADSLAG MELALUI METODE BAGIAN DALAM MENINGKATKAN HASIL BELAJAR SENAM: Indonesia - Azari, Al; Zulkifli (INSPIREE: Indonesian Sport Innovation Review, 2020)
The study purpose. The purpose of this study was to ditermine the use of the methods section on the floor gymnastics learning materials senior negeri 1 kepenuhan kabupaten rokan hulu. Materials and methods. The type of research that is used a Class Action research is conducted ( PTK ), which is conducted in class XII senior IPS1 Kepenuhan Kabupaten Rokan Hulu with a sample of 20 students. Data collection techniques used were test-performers students and teacher observation sheets. Data were analyzed with exposure between cycles Results. Based on the results of the initial data is of 20 studenst the are 14 studenst or 70% in category is not complete, ie 2 students or 20% of students scored at the category “ less good “, and 4 students or 20% of students scored at the category “ good “. Then the first cycle there are 8 students or 40% students in category “ good enough “ and the 10 students or 50% in the category “ good “ and 2 students or 10% in the category “ very good”. And the second cycle there are 18 students received grades due to the percentage 81,83%, 4 students “ very good “ or 20%, and 14 students or 20% “ good “ and 2 students or 10 % “less good”.in the second cycle occured in classical completeness increase significantly compared to the first cycle with the acquisition value reaches a minimum completeness criteria 9 KKM 75) Conclusions: Thus the analysis shows that the use of variety of sections method can improve learning outcomes radslag students on subjects penjasorkes XII senior grade students IPS1 Kepenuhan Kabupaten Rokan Hulu.